The Role of Fatigue in Return to Sport Testing Following Anterior Cruciate Ligament Reconstruction - Justin C Tallard; Corbin Hedt; Bradley S Lambert; Patrick C McCulloch (North American Sports Medicine Institute, 2021)
# Background Fatigue may play a role in anterior cruciate ligament (ACL) injury, but has not been incorporated into objective test batteries for return to sport decisions following ACL reconstruction (ACLR) surgery. The effect of fatigue on muscle function and performance following surgery and rehabilitation has been poorly studied. # Purpose/Hypothesis The purpose of this study was to assess the effect of fatigue on performance of various hop tests used in clinical rehabilitation settings by examining LSI scores. The authors hypothesized that participants will have worse limb symmetry index scores following the fatigue protocol and that the operative limb (ACLR) will have a greater decline in function than the non-operative limb (CON). # Study Design Cross-Sectional Study. # Methods Participants (n=21 \[Male = 15, Female = 6\]; AGE = 24.6 ± 9.3) were at least six months post ACLR and in rehabilitation. Testing was performed over two separate sessions in either a non-fatigued (NFS) or fatigued state (FS). In the FS, individuals performed a series of exercises to exhaust muscular endurance, strength, and power systems, after which they performed as battery of seven hop tests (single hop for distance, triple hop for distance, crossover hop for distance, 6-meter timed hop, lateral rotation hop for distance, medial rotation hop for distance, and vertical jump for height). A 2(limb) x 2(time) ANOVA was used to compare limbs between each state. # Results Differences between limbs (CON vs ACLR) were observed for all hop tests in the NFS whereby the ACLR limb was observed to have reduced performance (↓5.4-9.1%, *p* \<0.05). When tested in the FS, significant differences in performance between limbs remained for only the crossover (↓4.9%), medial rotation (↓7.1%), lateral rotation (↓5.5%), and vertical hop (↓10.0%)(*p*\<0.05). When comparing the NFS and FS states, only the CON limb was observed to have significant decreases in performance of the Triple Hop (↓7.4%), Crossover (↓8.7%), and Lateral Rotation (↓5.2%)(*p*\<0.05). # Conclusions Following ACL reconstruction, there appears to be a greater loss in jump performance in the CON limb in the FS. These findings suggest it may be crucial to consider and assess the endurance of both limbs rather than just the ACLR limb when determining readiness for return to play. # Level of Evidence Level 3